Psychophysical Evaluation of a Tactile Display Based on Coin Motors. Issue 12 (15th May 2018) - Stronks, H. Christiaan; Parker, Daniel J.; Stacey, Ashley; Barnes, Nick
Abstract: Tactile vision substitution devices present visual images as tactile representations on the skin. In this study we have tested the performance of a prototype 96‐tactor vibrotactile using a subset of 64 tactors. We have determined the tactile spatial acuity and intensity discrimination in 14 naïve subjects. Spatial acuity was determined using a grating acuity task. Subjects could successfully identify the orientation of horizontal and vertical gratings with an average psychophysical threshold of 120 mm. When diagonal gratings were included in the analysis, the median performance dropped below psychophysical threshold, but was still significantly above chance at gratings of 142 mm wide. Intensity discrimination yielded an average Weber fraction of 0.44, corresponding to 13 discernable "gray levels" in the available dynamic range. Interleaved stimulation of the motors did not significantly affect spatial acuity or intensity discrimination.